ANALISIS PERBANDINGAN PSAP NO. 4 CATATAN ATAS LAPORAN KEUANGAN DENGAN LAPORAN KEUANGAN KPP BEA CUKAI - REZA FACHRUDDIN, NIZAR Reza (Jurnal Akuntansi AKUNESA, 2012)
KPP Bea Cukai type Tanjung Perak Surabaya Municipality is one of the government agencies engaged in Export and Import Services. KPP Bea Cukai Tipe Madya Tanjung Perak Surabaya Municipality is the main area of Customs Tax service in and out of exports and imports. But in this discussion the author only gives an overview of review notes to financial statements. notes to the statements made to help make it more easier for users to read financial statements. Based on research results. it can be concluded that the notes to the financial statements on KPP Bea Cukai Tipe Madya Tanjung Perak Surabaya, in the formulation according to the PSAP number 4. In a review accompanying Notes to Financial Statements on KPP Bea Cukai Tipe Madya Tanjung Perak Surabaya already present in accordance with the PSAP number 4.Keywords: public sector accounting, government sector accounting